Juridical Review of the Reduction of Detention Period for Class IIB Tanjung Pura Prisoners - Benario Dasmilta Sembiring; Yasmirah Mandasari Saragih (International Journal of Sociology and Law, 2024)
The granting of remissions for drug convicts is based on the condition of the house detainees who are overcrowded by convicts due to over capacity. Granting remission is not applied to drug convicts involved in large-scale trafficking cases, especially for big producers and airports. Tightening remissions for extraordinary crimes (Extraordinary Crime), especially for convicts of narcotics cases in Indonesia because these crimes continue to increase from year to year.The purpose of this study is to find out the legal rules regarding remission for narcotics convicts, the implementation of granting remissions for narcotics convicts in class II B Tanjung Pura prison and the obstacles to implementing the disciplinary law for narcotics convicts in class IIB Tanjung Pura prison. This research is included in the analytical descriptive research with the type of normatif juridical research using qualitative analysis methods. Based on the results of the research, it is known that the legal basis used in granting remission is regulated in Law Number 12 of 1995 concerning Corrections, Presidential Decree Number 174 of 1999 concerning Remission, Presidential Decree Number 21 of 2005 given for extraordinary events, Government Regulations Number 99 of 2012 concerning the Second Amendment to Government Regulations Number 32 of 1999 concerning Requirements and Procedures for the Implementation of the Rights of Correctional Families, Minister of Law and Human Rights Number 18 of 2019 concerning Amendments to the Minister of Law and Human Rights Number 3 of 2018 concerning Terms and Procedures for Granting Remission, Assimilation, Leave to Visit Family, Parole, Leave Before Release, and Conditional Leave. Implementation of Granting Remission at the Langkat Class IIB Tanjung Pura Penitentiary refers to laws and regulations that regulate provisions regarding remissions, during 2020 973 general remissions were granted and 1039 special remissions, in 2021 1145 general remissions were granted and 1135 special remissions and in 2022 1908 general remissions were granted and special remissions as many as 1147 people as well as obstacles to the implementation of grants remissions to inmates at the Class IIB Tanjung Pura Correctional Institution come from ; internal factors such as prisoner behavior factors, human resource factors, facilities and infrastructure factors and external factors such as legal or juridical factors, administrative factors, institutional factors, and community factors.